STRATEGIC PEDAGOGICAL FRAMEWORK FOR TEACHING ONOMASTIC UNITS THROUGH LINGUOCULTUROLOGICAL INTEGRATION IN ENGLISH AND UZBEK CONTEXTS - Mamatkulova Bakhtijon Ravshanovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article proposes a strategic pedagogical framework for teaching onomastic  units  in  English  and  Uzbek  languages  through  linguoculturological integration. It focuses on the didactic potential of proper names as cultural markers and tools for developing intercultural awareness. The study introduces innovative strategic models,  including  discourse-based  instruction,  project-oriented  learning,  and cognitive-linguistic  analysis.  The  results  indicate  that  strategic  incorporation  of onomastic material into language teaching enhances learners’ pragmatic competence and  cultural  literacy.  The  paper  also  outlines  practical  classroom  strategies  and assessment tools for effective implementation.